ECB credibility and transparency - Geraats, Petra M.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission: Directorate-General for Economic and Financial Affairs, 2008)
This paper argues that ECB credibility in delivering price stability is being progressively eroded; this problem could be overcome by embracing greater transparency especially about the ECB's objectives, macroeconomic forecasts and decision-making. During the ECB's first decade, average inflation in the euro area has been low, but it has failed to meet the ECB's criterion of below but close to 2% over the medium term. Although this could be attributed to unanticipated shocks, the analysis in this paper points to some structural shortcomings. In particular, there has been an upward trend in medium and long term inflation expectations in the euro area, which have even reached over 2%, and the credibility of the ECB achieving price stability in the medium term has gradually eroded to critically low levels. In addition, there is evidence that medium and long term inflation expectations are negatively affected by the inflation experience of the euro area. However, this paper argues that these problems could be overcome embracing by greater transparency, especially about the ECB's objectives, macroeconomic forecasts and decision-making.
Economic Papers.